Plant-made vaccines and reagents for the One Health initiative - Edward Peter Rybicki (Taylor & Francis Group, 2017)
The One Health initiative is increasingly becoming a prominent discussion topic in animal and human health, with its focus on prevention of spread of zoonotic diseases, both in animals, and from animals to humans. An important part of One Health is that diagnostics and vaccines for diseases may be the same thing - and be used for both humans and animals. One potential problem standing in the way of wider adoption of One Health principles, though, is that use of conventional cell fermentation systems for production of the recombinant proteins that could be used as diagnostics or vaccines is often expensive and is not easily scalable. A solution to this may be the use of plants or plant cells as bioreactors: molecular farming, or the production of biologics in plants, is now a well-established science with many proofs of principle and important proofs of efficacy for especially animal vaccines. This review discusses how molecular farming could enable important advances in One Health, using as examples plant-made vacccines, reagents and therapeutics for influenza viruses, ebolaviruses, rabies virus, bunyaviruses and flaviviruses.